Gas chromatography mass spectrometry couple with quadrupole time-of-ﬂight (GC-QTOF MS) as a powerful tool for proﬁling of oxygenated sesquiterpenes in agarwood oil - Erny Haslina, Abd Latib; A.K.M., Moyeenul Huq; Seema, Zareen; Saiful Nizam, Tajuddin (Elsevier B.V., 2023)
Agarwood (Aquilaria malaccensis) is very well known as the most expensive wood in the world due to its wide applications in perfumery, cosmetic traditional medicine, and religious ceremonies. The study aimed to give an in-depth characterisation focusing on marker compounds in A. malaccensis from different places in Malaysia. The establishment of an oxygenated sesquiterpenes chemical profile of the fungus-infected agarwood oil was achieved by gas chromatography mass spectrometry (GC–MS) coupled with quadrupole time (QTOF) technique. Aroma compounds were identified as sesquiterpenes and oxygenated sesquiterpenes where agarospirol was found in samples of all locations (3.12%, 3.54%, 3.36% and 2.26% from Melaka, Pahang, Kelantan A and Kelantan B respectively) and also N-hexadecanoic acid as one of the major compounds. Both compounds were further isolated by Prep-GC and confirmed by NMR. This study provides a reference for agarwood oil analysis from different origins in Malaysia.